Análise proteômica de isolados de Leishmania (Leishmania) chagasi sensíveis e resistentes à miltefosina - Trindade, Juliana Brambilla Carnielli (2011)
Visceral leishmaniasis is a systemic disease that is fatal if untreated and is caused by the Leishmania donovani complex, which include the Leishmania (L.) chagasi. Visceral leishmaniasis treatment relies on a few chemotherapeutic drugs including Sb(V), amphotericin B and miltefosine. Miltefosine was recently approved as the first oral drug active against visceral leishmaniasis in India. Miltefosine resistance mechanisms are being elucidated in laboratory Leishmania spp. isolates but are less clear in clinical isolates. In this study, we used comparative two-dimensional gel electrophoresis and mass spectrometry methodologies to highlight and identify proteins that are differentially expressed between miltefosine-sensitive (S: S1 and S2) and resistant (R: R1 and R2) L. (L.) chagasi isolates from kala-azar patients included in clinical trial in Brazil, in order to assess the effectiveness of this drug. We describe here a high-resolution proteome for L. (L.) chagasi promastigotes comprising an average of 459 spots, which corresponds to 5,7% of gene products predicted for Leishmania spp. Following comparison of the whole proteome profiles between sensitive and resistant L. (L.) chagasi clinical field strains, 80 differentially expressed spots were detected. Eighteen spots were found to be specific of a sensitive group and only one of a resistant group, while 48 spots changed in intensity between these groups. The others spots were present in a unique isolates (7 in S1, 3 in S2 and 2 in R1) or in three isolates simultaneously (1 in S1, S2 e R1). MALDI/TOF-TOF mass spectrometry allowed the identification of 49 spots (61,3%) corresponding to 32 distinct protein and 7 hypothetical proteins. Among the proteins identified, the comparative proteomics screen highlighted two proteins, peroxidoxin (overexpressed in R group) and calpain-like cisteína peptidase (exclusively detected in S), differentially expressed, suggesting that programmed cell death is reduced in resistant parasite. These data suggest that these proteins may be related to resistance phenotype to miltefosine.